ANALYSIS OF TEMPERATURE EFFECT ON FALLING WEIGHT DEFLECTOMETER MEASUREMENTS - IDAYATI R, SRI
ANALYSIS OF TEMPERATURE EFFECT ON FALLING WEIGHT DEFLECTOMETER MEASUREMENTS, Idayati, Sri, 1992, Program Magister Sistem dan Teknik Jalan Raya, Program Pascasar Jana, Institute Tekrsologi Bandung. Non-Destructive Testing (NDT) and deflection testing are now universally recognized methods for the sufficient accurate and rapid structural evaluation of road pavements. The Falling Weight Deflectometer (FWD) is one of the testing equipment for non-destructive deflection measurement of testing. Temperature variation is one of the important factors to be considered in modern pavement structural design and this study concerns the measurements and analysis of the effect of temperature on flexible pavements using a Falling Weight Deflectometer equipment and the ELMOD program. Field work has consisted of pavement temperature measurements at 2.5 cm 7.5 cm and 12.5 cm, and deflection bowl measurements using a Falling Weight Deflectometer. Air temperature-measurements have been made in the immediate vicinity of the test site. All were done over 24 hours on given pavement structures. Air temperature data were collected also from 'Badan Meteorologi and Geofisika This result indicates that temperatures at certain pavement depths have a linear relationship with air temperature but the surface temperature fluctuates, as found at all test locations. An adjustment to the Witczak equation has been proposed for Indonesian pavement conditions. Linear relationships were obtained between pavement temperature and FWD maximum deflection, and exponential relationships between pavement temperature and asphalt layer modulus. Stiffness modulus calculations of asphalt mix as function of temperature using different methods ( i.e. VAN DER POEL , BONNAURE , THE ASPHALT INSTITUTE ) were also carried out and the results show that the BONNAURE relationship provides the closest comparison with stiffness modulus of asphalt mix derived from the ELMOD program.